Tales of the unexpected: Coping among female collegiate volleyball players - Holt, N. L.; Berg, K.-J.; Tamminen, K. A. (Research Quarterly for Exercise and Sport, 2007)
The purpose of this study was to examine patterns of appraisal, coping, and coping effectiveness in sport. Ten players from a collegiate female volleyball team were interviewed on two occasions, first in the week before a provincial final playoff tournament and in the week following the tournament. Data were transcribed verbatim and subjected to content and idiographic analyses. Athletes generally did not predict or anticipate the stressors they actually experienced during the tournament. Subjective appraisals of effective coping were associated with consistency between proactive and actual coping attempts. Reported effective coping was associated with the attainment of personal performance goals and use of cognitive, behavioral, and emotional coping strategies in the absence of behavioral avoidance. Reported ineffective and partially effective coping was associated with not attaining personal performance goals, and the use of cognitive coping strategies with behavioral avoidance. Finally, older, more experienced athletes reported they coped better than younger, less experienced athletes during the tournament.